Tecnologia e formação: o smartphone na experiência de jovens universitários - Ramos, Viviane de Assis (2018)
This master's research, developed in the postgraduate course of Program in Education, in the line of research Fundamentals of educational processes, aimed to analyze how smartphone technology mediates the daily experience of university students, in the family, at school, at work and among social groups in general. The smartphone is one of the most advanced information and communication technologies that is available and accessible for everyone and, as such, mediates social relations. In this work, technological rationality is analyzed as constitutive of human relations, changing the space-time dimensions as the indivuduals access information that circulates around the world and produce new forms of experience. The concept of experience, as proposed by Walter Benjamin, is used to support the thesis that the impoverishment of human possibility of experiencing formative processes is under way, from which the meanings of universality, humanity and autonomy derive. This impoverishment is related to the technical, technological and scientific advance, that has boosted the development of capitalist society, especially after the First World War when forms of sociability were constituted and produced important changes in the understanding and apprehension of time, space, memory and tradition. In order to understand this problem we sought the contributions of authors such as Karl Marx, Friedrich Engels, Sigmund Freud, Walter Benjamin, Max Horkheimer, Herbert Marcuse and Theodor Adorno, underpinning a critical analysis of the society of capital and about the instrumental and domain rationality. The research was developed as an exploratory study of qualitative characteristics, which used as a data collection instrument, a questionnaire, applied to university students, over 18 years old, from the Federal University of Goiás, from four different courses: Medicine, Law, Pedagogy and Physical Education. The results of this investigation shows how determinant the mediation of technology can be, in the form and content of social relations, especially in the experience of young people with one another, with the time, with the body and with the memory.